Pengaruh Persepsi Siswa Mengenai Kompentensi Pedagogik Guru Dan Komunikasi Guru Dengan Siswa Terhadap Motivasi Belajar Akuntansi Pada Siswa Kelas Xi Sma Negeri 1 GondangrejoTahun Ajaran 2015/2016 - PURNAMASARI, INDAH (2016)
PENGARUH PERSEPSI SISWA MENGENAI KOMPENTENSI PEDAGOGIK GURU DAN KOMUNIKASI GURU DENGAN SISWA TERHADAP MOTIVASI BELAJAR AKUNTANSI PADA SISWAKELAS XI SMA NEGERI 1 GONDANGREJO KARANGANYAR TAHUN AJARAN 2015/2016 INDAH PURNAMASARI, Budi Sutrisno Indah Purnamasari. A210110139.PENGARUH PERCEPTION OF STUDENT TEACHERS AND COMMUNICATION pedagogical TEACHER WITH STUDENT LEARNING MOTIVATION TO ACCOUNTING SISWAKELAS XI SMA Negeri 1 Gondangrejo KARANGANYAR ACADEMIC YEAR 2015 / 2016Program Studies Faculty of Accounting Education Teaching and Education University of Muhammadiyah Surakarta, 2015. The purpose of this study was to determine: 1) Effects of student perceptions pedagogic teachers on motivation to learn accounting in class XI SMA Negeri 1 Gondangrejo; 2) The effect of teacher communication with students' motivation to learn accounting in class XI SMA Negeri 1 Gondangrejo; 3) Effect of persepsis students regarding pedagogical competence of teachers and teacher communication with students' motivation to learn accounting in class XI SMA Negeri 1 Gondangrejo. This research includes associative quantitative research whose conclusions obtained based on the results of statistical analysis. This study took place in SMA Negeri 1 Gondangrejo Karangannyar. Data collection techniques by using documents and questionnaires that have been tested with normality test and reliability test. Analysis technique used is multiple regression. Results of regression analysis regression equation; Y = 11.349 + 0,233X1 + 0,431X2. Which means that the influence of perception student and teacher communication with students berpenagruh on motivation to learn accounting, based on the analysis and discussion can be concluded that: 1) Perceptions of students pedagogic influence the motivation to learn accounting teacher in class XI student of SMAN 1 Gondangrejo. It is evident from analysis memperolehthitung> ttable, namely 3.033> 1.984 (α = 5%) and the significance value <0.05, namely 0.003 with the relative contribution of 26.9% and the effective contribution of 9.7%. 2) Communication with teachers affects student motivation to learn accounting students of class XI SMA Negeri 1 Gondangrejo. This is evident from the results of the regression analysis obtained thitung> ttable, namely 5.734> 1.984 (α = 5%) and the significance value <0.05, namely 0.000 with the relative contribution of 73.3% and the effective contribution of 26.51%. 3) Perceptions of students pedagogic teachers and teacher communication with students' motivation to learn accounting memepengaruhi in class XI SMA Negeri 1 Gondangrejo. This was proved by the regression results obtained Fhitung> Ftable is 27.678> 3.07 with a significance value <0.05 is 0.000. Variables Perceptions of students pedagogic teachers contribute effectively to 9.79%. Variable teacher communication with students provide effective sumabangan 26.51%. So that the total effective both by 36.3%. While 63.7% are influenced by other variables not examined. In this study teacher communication with students more dominant motivation to learn accounting in class XI SMA Negeri 1 Gondnagrejo. Keywords: Perception of Students, Teachers Communication, Motivation